2018
DOI: 10.1103/physrevb.97.054420
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation of magnetocrystalline anisotropy oscillations in Co2FeAl/Ta heterostructures

Abstract: We report first-principles investigations of magnetocrystalline anisotropy energy (MCAE) oscillations as a function of capping layer thickness in Heusler alloy Co2FeAl/Ta heterostructures. Substantial oscillation is observed in FeAl-interface structure. According to k-space and band-decomposed charge density analyses, this oscillation is mainly attributed to the Fermi-energy-vicinal quantum well states (QWS) which are confined between Co2FeAl/Ta interface and Ta/vacuum surface. The smaller oscillation magnitud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…We have carefully chosen the ranges of distortions to see the trends of the density of states and their effect on half-metallicity, as these properties are highly sensitive to the distortions applied. Numerous reports on band structures are available on unstrained (i.e., cubic) cases based on the Co 2 FeAl alloy [43,51,[54][55][56][57][58][59][60]. However, some of our calculation results must be addressed in predicting the device compatibility under uniform-strain and tetragonal distortions.…”
Section: Effect Of Lattice Distortions On the Electronic And Magnetic...mentioning
confidence: 99%
“…We have carefully chosen the ranges of distortions to see the trends of the density of states and their effect on half-metallicity, as these properties are highly sensitive to the distortions applied. Numerous reports on band structures are available on unstrained (i.e., cubic) cases based on the Co 2 FeAl alloy [43,51,[54][55][56][57][58][59][60]. However, some of our calculation results must be addressed in predicting the device compatibility under uniform-strain and tetragonal distortions.…”
Section: Effect Of Lattice Distortions On the Electronic And Magnetic...mentioning
confidence: 99%
“…Another merit of FT is that by Equ. ( 14) some k-space resolved analyses can be performed, such as the contribution of the quantum well states to the oscillation of MCAE [10].…”
Section: Mcaementioning
confidence: 99%
“…Usually, the MCAE is on the order of meV at surfaces and interfaces [4,5,6], about 3 orders of magnitude larger than that of bulk crystals [7,1]. Apart from the interest in fundamental science, the practical applications have also stimulated lots of research into the understanding and optimization of MCAE [8,9,10,11,12,13]. One of the applications is the magnetic tunnel junction (MTJ), which is the core structure of magnetic random access memory (MRAM) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…We studied Fe2CoAl Heusler alloy and found that XA ordered structure was much more stable than the regular L21 structure [26,27]. The comprehensive theoretical reports are available on L21 ordered Co2FeAl Heusler alloy [28][29][30][31][32][33][34]. However, a proper understanding of the site preferences of 3d atoms in their respective structures (L21 and XA) is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%